Liquidity And Profitability Analysis To Assess The Financial Performance Of Listed Telecommunications Companies On The Indonesia Stock Exchange Period 2019 – 2023 - Indah Permata Sari Sitorus Pane; Cahyo Pramono (Yayasan Multidimensi Kreatif, 2025)
The development of telecommunications in Indonesia shows significant growth, reflected in the increase in mobile phone ownership, from 50.94% in 2013 to 67.29% in 2023. However, telecommunications companies are faced with the challenge of maintaining sound financial performance to support the development of new infrastructure and technologies. This study aims to analyze the liquidity and profitability ratios of telecommunication companies listed on the Indonesia Stock Exchange (IDX) in the 2019–2023 period, to assess their financial performance. Data shows an increase in liquidity ratios, such as the Current Ratio which increased from 67.30% in 2020 to 88.68% in 2022, which reflects a better ability to meet short-term obligations. The Quick Ratio also increased, while the Cash Ratio remained stable at 43%. However, on the profitability side, ratios such as Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE) declined during the period, indicating a decrease in efficiency in generating profits from revenue, assets, and equity. The results of this study show that although telecommunication companies such as PT Telkom Indonesia Tbk show stable financial performance, they are still experiencing pressure on liquidity. On the other hand, PT Indosat and PT XL Axiata experienced challenges in maintaining profitability, but began to recover in 2022–2023 thanks to operational efficiency and strategic investments. This research provides important insights into the factors affecting financial performance in the telecommunications sector and provides recommendations to improve the competitiveness of companies in an increasingly competitive market.